SOSIALISASI DAN PENYULUHAN NARKOBA - Mellisa Fitri (UII, 2014)
One of the problems that occur among adolescents is drug abuse. Drug abuse isincreasing from year to year and is based on a survey of the National Narcotics Agency(BNN) approximately 90% of drug abusers are trying to use is among students orstudents. Drug abuse amongstudents or students will negatively affect the sustainabilityof national development. One of the things that cause students or students abusingdrugs is the lack of information about the dangers of drugs. One of the efforts beingmade to provide information about the dangers of drugs is through education with thelecture method. Most of some villagers Tumut, the Village whole observatories, DistrictSelo, Boyolali is among teenagers and children's status as a student or already workingwho need educationabout the effects and dangers of drug use. This extension adds toawareness of youth and children of the dangers of drug abuse. As well as increasingawareness of parents to provide oversight and more attention to their children.